The human side of enterprise - McGregor, Douglas (New York Mcgraw-Hill, 2006)
So began Douglas McGregor in this 1960 management classic. It was a seemingly simple question he asked, yet it led to a fundamental revolution in management. Today, with the rise of the global economy, the information revolution, and the growth of knowledge-driven work, McGregor's simple but provocative question continues to resonate-perhaps more powerfully than ever before.
Includes bibliographical references and index.
Keywords: Personnel management